Rehabilitasi Sebagai Bentuk Upaya Pemulihan (Kuratif) Secara Medis Dan Yuridis Bagi Korban Penyalahgunaan Narkotika - Bastianto Nugroho; agung putri harsa satya nugraha (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Rehabilitation can be used as a depenalization effort for narcotics addicts because each addict is a person who is physically ill and mentally ill, because of his addiction to narcotics. He must be looking for the fulfillment of narcotics needs in any way, so that narcotics abusers need to be rehabilitated and treated rather than he must be placed in a Lembaga Pemasyarakatan (LAPAS). Because it was feared he would continue to commit other new criminal acts within the prison, such as the practice of bribery with unscrupulous persons, committing violence and becoming a murderer, even becoming part of a narcotics drug syndicate within a correctional facility that often happens recently. So it is sought for those who become narcotics abusers to be channeled to the Rehabilitation Institute center to be treated. Rehabilitation as a depenalization effort for narcotics addicts certainly has many advantages. Beyond the focus on the purpose of criminal prosecution of narcotics crime cases, where rehabilitation can be used as an alternative way so that correctional Institutions considered to be no longer able to accommodate inmates can be included in the Rehabilitation Institution. Rehabilitation is considered effective in resolving problems related to narcotics abuse and illicit trafficking in Indonesia. The approach used in this study is the statute approach because this research takes the focus of various legal rules that are the central theme of the study. The proposed statutory approach is also called the juridical normative approach or socio legal research.